Actuación de los caciques en las haciendas de Riobamba a fines del siglo VXIII - Guambo Villa, Miryan Carolina (2022)
The objective of this research was to analyze the actions of the caciques in the Riobamba haciendas at the end of the 18th century. The cacicazgo was implemented by the Spaniards to generate territorial demarcations and control, to collect taxes from people who worked on the haciendas. This research had a non-experimental design, we use the bibliographic method, an analytical type, and descriptive level; The instrument used was the descriptive file that allowed allow us to know the participation of the caciques in the haciendas at the end of the 18th century; which led us to the conclusion that, during the eighteenth century, the indigenous people surrounding the city of Riobamba, had great economic difficulties. Since the salaries they received, for their job, were minimal, compared to the taxes they had to pay, many of them were dispossessed of their own land, and without options serve the landowners. The political situation of the indigenous people was very poor, since they had neither a voice nor a vote in the decisions made by the Spanish Crown. However, there were indigenous uprisings that improved their economic quality, but in a minimal way like receiving an increase in their salaries, rest days and many of them even managed to recover their land, although this postulate cannot be generalized in all contexts, because it depends on time and space.